A Review on Smart Home Using IoT (International Journal of Innovative Research in Computer Science & Technology, 2021)
Mobile gadgets have become an integral  part of our daily lives. The last several years. As a result,  providing facilities and services is essential. On the internet,  security is becoming more important. Android mobile  interacts with automated system devices. The system and  mobile device may communicate with one another. Wi-Fi  allows them to communicate with one another. The  smartphone app may be downloaded and connected to the  system from any device that is suitable. Lights, fans, and  other electrical equipment may be turned on and off using  commands. Air conditioners, etc., as well as setting a timer  at home or anywhere else from a mobile device, an  organization may be delivered fast and simply. Devices through a user-friendly graphical user interface (GUI), which  is any average user will find it simple to use. After that, the  system takes action. Respond to these commands by  performing the actions specified in the commands and  informs the user of the outcome is also visible to the user.  Within the Wi-Fi range of an Android mobile application.  As a result, designing a home automation system is a good  choice. A luxury lifestyle aimed at creating a cutting-edge  house Wi-Fi technology is used to create an automation  system.
Keywords: Arduino; Automation; IoT; Smart Home; Wi-Fi